Antecedent Trust and Customer Satisfaction to Repurchase Intention Digital Payment Electronic Data Capture Yokke Bank Himbara Medan - Hendra Sitepu, Jhoni; Darwin Lie; Anton A.P. Sinaga (International Journal of Computational and Experimental Science and Engineering, 2025)
This study aims to examine the effect of Perceived Ease Of Use on Purchase Intention through trust and Costumer Satisfaction both directly and indirectly. Quantitative paradigm and deductive reasoning are used in this study. The population in this study were all people of North Sumatra who use digital payment Electronic Data Capture Yokke Bank Himbara Medan and a research sample of 390 people who use digital payment Electronic Data Capture Yokke Bank Himbara Medan on MSMEs. The data collected in this study were analyzed using the structural equation method based on PLS-SEM. The results show that all hypotheses submitted are accepted. Directly Perceived Ease Of Use, trust and Costumer Satisfaction have a significant effect on Purchase Intention. Furthermore, Perceived Ease Of Use has a significant effect on trust and Costumer Satisfaction, and indirectly trust and Costumer Satisfaction mediate the effect of Perceived Ease Of Use on Purchase Intention digital payment Electronic Data Capture Yokke Bank Himbara Medan.